IMF Staff papers : Volume 32 No. 3. - International Monetary Fund. Research Dept. (Washington, D.C. : International Monetary Fund, 1985)
The purpose of this paper is to outline a theoretical framework that can serve as a starting point for analyzing interest rate behavior in those developing countries that are in the process of removing controls on the financial sector and restrictions on capital flows. The approach suggested here combines elements of models developed for both closed and open economies; thus, it is able to incorporate the influences on domestic interest rates of foreign interest rates, expected changes in exchange rates, and domestic monetary developments. An interesting feature of the model presented is that the approximate degree of financial openness, defined as the extent to which domestic interest rates are linked to foreign interest rates, can be determined from the data of the country analyzed. The estimates indicate that in Colombia both foreign and domestic factors are important, whereas domestic interest rates in Singapore are fully determined by foreign interest rates and by variations in the exchange rate. These results are precisely those expected, given the characteristics of the respective financial systems in the two countries.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet